2016
DOI: 10.1080/17549507.2016.1216601
|View full text |Cite
|
Sign up to set email alerts
|

Intonation patterns in older children with cerebral palsy before and after speech intervention

Abstract: The findings highlight that changes can occur in the use of intonation patterns in children with dysarthria and CP following speech systems intervention. It is hypothesised that the emergence of the rising pattern in some of the children's intonational inventories possibly reflected improved breath support and control of laryngeal muscles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Prosody is often affected, with the nature of the disturbance depending on the language. Specific effects have been described for intonation and stress patterns in English (Kuschmann et al, 2017;Patel, 2003Patel, , 2004Patel, Hustad, Connaghan, & Furr, 2012), tone production in Cantonese (Ciocca, Whitehill, & Ng, 2002;Ciocca, Whitehill, & Yin, 2004), tone production in Mandarin (Jeng et al, 2006), prosody in German (Schölderle et al, 2016), and prosody in Spanish (Puyuelo & Rondal, 2005). It is clear from these studies that prosody is a vulnerable feature of the speech disorder in CP, and cross-language comparisons may illuminate language variations in these disturbances.…”
Section: Effects Of Cp On Speech Production Across Languagesmentioning
confidence: 88%
See 1 more Smart Citation
“…Prosody is often affected, with the nature of the disturbance depending on the language. Specific effects have been described for intonation and stress patterns in English (Kuschmann et al, 2017;Patel, 2003Patel, , 2004Patel, Hustad, Connaghan, & Furr, 2012), tone production in Cantonese (Ciocca, Whitehill, & Ng, 2002;Ciocca, Whitehill, & Yin, 2004), tone production in Mandarin (Jeng et al, 2006), prosody in German (Schölderle et al, 2016), and prosody in Spanish (Puyuelo & Rondal, 2005). It is clear from these studies that prosody is a vulnerable feature of the speech disorder in CP, and cross-language comparisons may illuminate language variations in these disturbances.…”
Section: Effects Of Cp On Speech Production Across Languagesmentioning
confidence: 88%
“…Moreover, it is important to understand how interventions targeting a particular subsystem lead to improvements in speech intelligibility or quality. Promising results have been reported in several studies (Kuschmann, Miller, Lowit, & Pennington, 2017;Levy, 2014;Miller et al, 2014;Netsell, 1984;Netsell & Daniel, 1979;Pennington, Miller, Robson, & Steen, 2010).…”
mentioning
confidence: 81%
“…We previously observed modest changes in overall voice quality, speech rate, pitch and intensity (perceived by listeners as loudness), which were insufficient to account for changes in intelligibility. 16 This study will examine if the increased intelligibility observed in some children following intervention focussing on breath support and speech rate is associated with the ability to differentiate individual sounds within words.…”
Section: Fundingmentioning
confidence: 99%
“…After the Speech Systems Approach, children produced longer breath groups (mean = 1.1 sec) and produced more syllables per second, 37 but the melodic intonation of their speech showed no change. 16 Children's voice was rated as stronger after the Speech Systems Approach on the GRBAS (Grade, Roughness, Breathiness, Asthenia, Scale) four-point rating scale of voice disorder, 54 by therapists blinded to the time of recordings (mean reduction in asthenia was 0.3). 55 The impact of individual acoustic changes following LSVT on children's intelligibility has not been tested to date.…”
Section: Evidence Reviewmentioning
confidence: 99%
“…Respiratory and phonatory deficits may include reduced respiratory control, difficulty with coordination of respiration and phonation (Pennington et al., 2018), reduced vocal intensity (Allison & Hustad, 2018), reduced vocal quality, and impaired variation and control of fundamental frequency (Pennington et al., 2010a; Schölderle et al., 2016). Resonance and prosodic impairment have also been documented among individuals with CP, characterized by hyper‐ or hypo‐nasality (Schölderle et al., 2016), as well as reduced speech rate and impaired intonational patterns (Allison & Hustad, 2018; Kuschmann et al., 2017), respectively. Articulatory deficits are typically characterized by impaired production of both consonants (Allison & Hustad, 2018; Ansel & Kent, 1992) and vowels (Higgins & Hodge, 2002; Levy et al., 2016).…”
Section: Speech Production In Cerebral Palsymentioning
confidence: 99%